Application of passive modified atmosphere packaging in the preservation of sweet corns at ambient temperature. (January 2021) - Liu, Hui; Li, Dongli; Xu, Wencai; Fu, Yabo; Liao, Ruijuan; Shi, Jiazi; Chen, Yunzhi
Abstract: The purpose of this study was to design a passive modified atmosphere packaging (PMAP) to effectively extend the shelf-life of fresh sweet corn under ambient temperatures. Oxygen permeable film (OPF) and water vapor permeable film (WPF) of different areas were used to prepare the PMAPs. By changing the areas of the OPF and WPF, different headspace atmospheres could be created in the PMAPs, and the effects of different atmospheres on the quality of sweet corn could be evaluated. The experiments were carried out under the temperature conditions of 25 ± 1 °C and relative humidity conditions of 60 ± 5%. The headspace gas, weight loss rate, hardness, total soluble solids content, total acid content, vitamin C content, and sensory quality were measured daily. The results showed that when the proportional area of WPF was 80%–85% and OPF was 15%–20%, the PMAP created a suitable atmosphere for fresh sweet corn, extending the shelf-life to 5 days at ambient temperature. Highlights: OPF and WPF were made into PMAP according to different area ratios. Low O2 concentration, high CO2 concentration and high humidity were formed. The shelf life of sweet corn at ambient temperature was extended to 5 days. PMAP provided conditions for storage, transportation and sale of sweet corns.